2012
DOI: 10.1021/pr201244t
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Identification of Cerebrospinal Fluid Proteins in a Rat EAE Model of Multiple Sclerosis

Abstract: The experimental autoimmune encephalomyelitis (EAE) model resembles certain aspects of multiple sclerosis (MScl), with common features such as motor dysfunction, axonal degradation, and infiltration of T-cells. We studied the cerebrospinal fluid (CSF) proteome in the EAE rat model to identify proteomic changes relevant for MScl disease pathology. EAE was induced in male Lewis rats by injection of myelin basic protein (MBP) together with complete Freund's adjuvant (CFA). An inflammatory control group was inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 83 publications
4
40
0
Order By: Relevance
“…Biological Significance of the Putative Disease Markers Detected in the Spinal Cord-Elevated levels of known protein members of the coagulation cascade such as fibrinogen (alpha, beta, and gamma isoforms) and kininogen-1, were identified by both spectral counting analysis and MS 1 -based quantification in the diseased spinal cord, observations that have previously been made by proteomic analyses of chronic active plaques isolated from post-mortem MScl brain tissue (12) and CSF from the MBP-EAE model (28). In concordance with other studies, we also identified increased levels of vitamin-d-binding protein (Vdbp), several protein members of the immunoproteasome, and multiple isoforms of immunoglobulin G (IgG) within the diseased spinal cord by both label-free quantification methods.…”
Section: Molecular and Cellular Proteomics 133mentioning
confidence: 83%
See 1 more Smart Citation
“…Biological Significance of the Putative Disease Markers Detected in the Spinal Cord-Elevated levels of known protein members of the coagulation cascade such as fibrinogen (alpha, beta, and gamma isoforms) and kininogen-1, were identified by both spectral counting analysis and MS 1 -based quantification in the diseased spinal cord, observations that have previously been made by proteomic analyses of chronic active plaques isolated from post-mortem MScl brain tissue (12) and CSF from the MBP-EAE model (28). In concordance with other studies, we also identified increased levels of vitamin-d-binding protein (Vdbp), several protein members of the immunoproteasome, and multiple isoforms of immunoglobulin G (IgG) within the diseased spinal cord by both label-free quantification methods.…”
Section: Molecular and Cellular Proteomics 133mentioning
confidence: 83%
“…Rosenling and colleagues recently identified 44 differentially abundant proteins within the CSF of a rodent EAE model of which only two were validated by MRM (28). In this study, three to four unique peptides served as protein surrogates in the MRM-based validation of candidate disease markers with the best four transitions per peptide monitored.…”
Section: Candidate Biomarker Validation By Targeted Mass Spectrometrymentioning
confidence: 96%
“…170,171 In a proteomic study, among a set of 44 proteins that discriminated experimental autoimmune encephalomyelitis (EAE) rats from control groups, GPx3 was increased in EAE animals. 172 Selenium levels tend to decrease in MS, as observed in a cohorts of Iranian 173 and Polish patients. 174 Complementing the suggestive data regarding a role of Se in MS pathogenesis, Chanaday et al 66 observed that treatment with diphenyl diselenide to the EAE animal model reduced signs of the disease phenotype, partly by preventing the reduction in body weight that accompanies the disease progression and decreased the time and the severity of symptoms.…”
Section: Other Neurodegenerative Diseasesmentioning
confidence: 87%
“…AFM has been shown to be a specific binding protein for vitamin E (Lichenstein et al, 1994). Also, it has been reported that AFM had the effect of neuroprotection (Heiser et al, 2002) and possible marker for various neurological pathologies including Alzheimer's disease and multiple sclerosis (Ringman et al, 2012;Rosenling et al, 2012). Diseases including pregnancy complications (Hubalek et al, 2014), metabolic syndrome (diabetes mellitus, obesity and hypertension), polycystic ovary syndrome (Koninger et al, 2014) have been showed associated with AFM as well.…”
Section: Discussionmentioning
confidence: 98%